A general higher-order nonlocal couple stress based beam model for vibration analysis of porous nanocrystalline nanobeams. (December 2017) - Ebrahimi, Farzad; Barati, Mohammad Reza
Abstract: This paper develops a higher order refined beam model with a parabolic shear strain function for vibration analysis of porous nanocrystalline nanobeams based on nonlocal couple stress theory. Nanocrystalline nanobeam is composed from three phases which are nano-grains, nano-voids and interface. Nano-voids or porosities inside the material have a stiffness-softening impact on the nanobeam. Nonlocal elasticity theory of Eringen is applied in analysis of nanocrystalline nanobeams for the first time. Also, modified couple stress theory is employed to capture grains rigid rotations. The governing equations obtained from Hamilton's principle are solved applying an analytical approach which satisfies various boundary conditions. The reliability of present approach is verified by comparing obtained results with those provided in literature. Finally the influences of nonlocal parameter, couple stress, grain size, porosities and shear deformation on the vibration characteristics of nanocrystalline nanobeams are explored. Highlights: It is the first time to study the vibration analysis of porous nanocrystalline nanobeams based on nonlocal couple stress theory. The essential measures to describe the real material structure of nanocrystalline nanobeams and the size effects were incorporated. This non-classical nanobeam model contains couple stress effect to capture grains micro-rotations. Nanocrystalline nanobeam is composed from three phases which are nano-grains, nano-voids and interface. The influences of nonlocal parameter, couple stress, grain size, porosities and shear deformation on the vibration characteristics of nanocrystalline nanobeams are explored.